Putting the bumps in the rocky road: optimizing the pathway to excellence - Collins, D. J.; Macnamara, A.; McCarthy, N. (Frontiers in Psychology, 2016)
There seems to be general agreement on the importance of challenge for effective development on the athlete pathway. What seems less coherent, however, are ideas on how much, when and how this challenge should be used. Reflecting our own experience as applied practitioners and our ongoing research, we offer a perspective on this work from a practitioner stance. The literature suggests that differences between levels of adult achievement relate more to what performers bring to the challenges than what they experience. Therefore, it is essential that young athletes have the opportunity to develop psycho-behavioral and coping skills, and have adequate social support, to ensure that adversity is interpreted as a positive growth experience. A periodized and progressive set of challenge, preceded with specific skill development, would seem to offer the best pathway to success. The importance of preparing athletes for challenges, supporting them through the experience, and then encouraging positive evaluation and reflection is key to successful outcome. Finally, we offer some suggestions, structures and systems, which can be used to support the skill-based approach promoted.